Bridging cultures through co-creation Dusun folklore in visualizations - Fun, Hannah Kong Nyuk; Imelda Ann Achin; Mohammad Puad Bebit (Akademi Seni dan Teknologi Kreatif, Universiti Malaysia Sabah, 2024)
The preservation and revitalization of the cultural narratives of the Dusun people can be achieved through the medium of visual arts. In a time when new influences are posing a threat to traditional storytelling, digital visual art offers a dynamic way to conserve and transmit these cultural narratives. The collections of indigenous Sabah folklore are concerningly dwindling, despite the fact that efforts to preserve digital stories and tactics are still in their early stages. This research aims to investigate the rich folklore of the Dusun culture in order to identify narratives that can be translating as digital visual art through the co-creation models. Visual representations of the Dusun folklore will be generated in collaboration with artists and people of the Dusun community, and the significance of these depictions is then interpreted through the approaches of archetypal theory. The study assesses the effectiveness of the co-creation technique to accurately describe and capture the Dusun cultural narratives. It aims to promote and advance the rich history of the Dusun people by integrating visual arts and cultural studies, providing new perspectives on cultural narratives. This research is expected to give a deeper understanding and meanings in the narratives of Dusun folklore through the lens of archetypal theory and assess the effectiveness of co-creation models in preserving and convey the Dusun cultural narratives. This study increases community engagement in cultural preservation and offers vital insights into how to effectively integrate traditional narratives with current artistic practices through innovative techniques of bringing them into the present.